Ecology and evolution of plant diversity in the endangered campo rupestre: a neglected conservation priority - Silveira, Fernando A. O.; Negreiros, Daniel; Barbosa, Newton P. U.; Buisson, Elise; Carmo, Flávio F.; Carstensen, Daniel W.; Conceição, Abel A.; Cornelissen, Tatiana G.; Echternacht, Livia; Fernandes, G. Wilson; Garcia, Queila S.; Guerra, Tadeu J.; et al. (Plant and soil, 2016)
BACKGROUND: Botanists, ecologists and evolutionary biologists are familiar with the astonishing species richness and endemism of the fynbos of the Cape Floristic Region and the ancient and unique flora of the kwongkan of south-western Australia. These regions represent old climatically-buffered infertile landscapes (OCBILs) that are the basis of a general hypothesis to explain their richness and endemism. However, few ecologists are familiar with the campo rupestre of central and eastern Brazil, an extremely old mountaintop ecosystem that is both a museum of ancient lineages and a cradle of continuing diversification of endemic lineages. SCOPE: Diversification of some lineages of campo rupestre pre-dates diversification of lowland cerrado, suggesting it may be the most ancient open vegetation in eastern South America. This vegetation comprises more than 5000 plant species, nearly 15 % of Brazil’s plant diversity, in an area corresponding to 0.78 % of its surface. Reviewing empirical data, we scrutinise five predictions of the OCBIL theory, and show that campo rupestre is fully comparable to and remarkably convergent with both fynbos and kwongkan, and fulfills the criteria for a classic OCBIL. CONCLUSIONS: The increasing threats to campo rupestre are compromising ecosystem services and we argue for the implementation of more effective conservation and restoration strategies.